2020 IEEE International Conference on Teaching, Assessment, and Learning for Engineering (TALE) 2020
DOI: 10.1109/tale48869.2020.9368316
|View full text |Cite
|
Sign up to set email alerts
|

Facebook’s Social Learning Group for Undergraduate Engineering Courses: A Case Study of Emergency Remote Teaching Amid Large Digital Divide

Abstract: platform for such a fully online setup. Such exploration became crucial in the face of the COVID-19 pandemic as institutions worldwide were forced to adopt emergency remote teaching.The COVID-19 pandemic has stricken almost all countries around the world. With governments implementing lockdown and quarantine measures, regular on-campus classes in schools, colleges, universities, and other educational institutions had come to a halt suddenly for many communities. Closure of educational institutions has affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…With regard to course design on an LMS, given that those who are negatively impacted by the digital divide are more likely to be smartphone dependent (Tsetsi and Rains, 2017), another strategy for reducing the gap could be to create more course content which is suitable for devices with small screens. Providing pre-recorded content which may be viewed asynchronously may also prove beneficial (Amir et al , 2020). The indicators that we propose may also be used to produce guidelines for the design of LMS courses, so that they are sensitive to the needs of learners with unreliable internet connections.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to course design on an LMS, given that those who are negatively impacted by the digital divide are more likely to be smartphone dependent (Tsetsi and Rains, 2017), another strategy for reducing the gap could be to create more course content which is suitable for devices with small screens. Providing pre-recorded content which may be viewed asynchronously may also prove beneficial (Amir et al , 2020). The indicators that we propose may also be used to produce guidelines for the design of LMS courses, so that they are sensitive to the needs of learners with unreliable internet connections.…”
Section: Discussionmentioning
confidence: 99%
“…In countries such as Cameroon (Beché 2020) and Ghana (Agormedah et al 2020), interventions such as televised classes, chat-based learning, posting course-packs and notes and baseline technology such as Unstructured Supplementary Service Data (USSD) services could be used to support the transition to ERT by offering learning, resources and information at reduced cost and complexity. Amir et al (2020) found that lecturers and educational planners had to consider an array of issues in deciding which platforms to use to continue teaching and learning under ERT conditions, as well as the potential barriers to entry for students and staff. In Bangladesh, this meant recognising that data costs and internet speed would be a hindrance for many students, especially those in rural areas, with the result that lecturers opted to use Facebook social learning groups as a feasible alternative, both for the platform's zero-rating options as well as its ubiquity as a social network in the country.…”
Section: The Pandemic Ert and Inequitymentioning
confidence: 99%
“…The notion of a "learning curve" was highlighted in the data, with staff needing to participate in increased professional learning and curriculum planning that incorporated available and emergent learning platforms and resources. As described in Amir et al (2020), often the tools that faculty planned around turned out to be incompatible with what students had available, meaning that adjustments regularly needed to be made to expand the opportunities available for learning and to find effective ways to track that this was taking place.…”
Section: The Transition To Ert and Blended Learningmentioning
confidence: 99%
“…Furthermore, educationalists accepted educational-based technologies because they provided them with the flexibility to deliver instructions [1], [70], and [71]. ICTs assist teachers with obtaining information easily and swiftly and make teaching and learning more interesting [72].…”
Section: Teachers' Perceptions Of Icts For Epsmentioning
confidence: 99%